1962
DOI: 10.1111/j.1744-7348.1962.tb05992.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of bulbiformin in soil

Abstract: SUMMARY Bacillus subtilis is capable of producing the antibiotic bulbiformin in soil. Antibiotic production is considerably enhanced when the soil is sterile and enriched with nutrients such as aspartic acid or asparagin, and dextrose or certain root residues. In the presence of the root supplements the antibiotic persists in soil over several weeks in fairly high concentrations.Under favourable conditions for antibiotic production such as the presence of root residues, inoculation of B. subtilis into soil res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1963
1963
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Seed treatment with B. subiilis significantly reduced incidence of fusarium wilt of pigeonpea. Vasudeva et al (1962) reported a reduction in pigeonpea wilt with both B. subtilis and its culture filtrate. It was proposed that the biocontrol activity could be due to systemic spread of an antifungal compound, bulbiformin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seed treatment with B. subiilis significantly reduced incidence of fusarium wilt of pigeonpea. Vasudeva et al (1962) reported a reduction in pigeonpea wilt with both B. subtilis and its culture filtrate. It was proposed that the biocontrol activity could be due to systemic spread of an antifungal compound, bulbiformin.…”
Section: Discussionmentioning
confidence: 99%
“…Wilt is an economically important vascular disease of pigeonpea caused by Fusarium udum. Vasudeva et al (1962) explained low incidence of fusarial wilt of pigeon-256 PoDiLE and LAXMI pea to be due to suppression of F. udum by Bacillus subtilis, which released an antibiotic in the rhizosphere. Seedlings of pigeonpea gained resistance to F. uduminfection due to the activity of bulbifonnin when the seeds bacterized with B. subtilis before sowing (Singh et al.…”
Section: Introductionmentioning
confidence: 99%
“…An experiment on the production of relative amounts of bulbiformin in sterile soil amended with different nutrients showed only 72 dilution units (Vasudeva et al 1962) of bulbiformin in 25 g. of dextrose-supplemented soil in a 7-day period, whereas in a comparable test using molasses the production was 380 D.U. The significant effect of molasses in enhancing the production of bulbiformin in soil was further confirmed by replacing dextrose with molasses in a dextrose-asparagine-phosphate medium where also the increase was about four times.…”
Section: Production Of Bulbiformin In Sterile Soilmentioning
confidence: 98%
“…In the experiments on the production of bulbiformin in normal field soil, using the n-butanol extraction method, no antibiotic could be detected. This was probably due to the fact that the efficacy of the extraction procedure is only 50 % (Vasudeva et al 1962), so it is not adequate to detect the relatively low quantities of the antibiotic. The antibiotic activity was, however, demonstrated by Chinn's (1953) slide burial technique.…”
Section: Production Of Bulbiformin In Sterile Soilmentioning
confidence: 99%
See 1 more Smart Citation